A history of civil litigation political and economic perspectives - Vandall, Frank J. (New York ; Oxford : Oxford University Press, 2011)
This text studies the expansion of civil liability from 1466 to 1980, and the cessation of that growth in 1980. It evaluates the creation of tort causes of action during the period of 1400-1980. Re-evaluation and limitation of those developments from 1980, to the present, are specifically considered.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Liability (Law) -- United States -- History; Strict liability -- United States -- History; Products liability -- United States -- History; Corporate power -- United States; Legislation -- United States